Pengembangan Sistem Informasi Dokumentasi Budaya dan Pengelolaan Dokumen Legalitas Kesenian Reyog Ponorogo Berbasis Web Menggunakan Metode Rapid Application Development - Fauzan Yuda Ayub Wijanarko; Rauhulloh Ayatulloh Khomeini Noor Bintang (TIN: Terapan Informatika Nusantara, 2026)
The management of art studio data and legal documents related to Reyog Ponorogo cultural heritage is still conducted manually, resulting in difficulties in archive retrieval, risks of document loss, and limited public access to cultural information. Furthermore, there is currently no integrated platform capable of combining cultural documentation and legal document management within a centralized digital system. This study aims to develop a web-based information system for cultural documentation and legal document management of Reyog Ponorogo to support cultural digitalization and improve document archiving processes. The research employed the Research and Development (R&D) method using the Rapid Application Development (RAD) model, which consists of requirements analysis, system design, implementation, and testing phases. The system was developed using the Laravel framework, Model View Controller (MVC) architecture, and a MySQL database. The main features include art studio data management, legal document uploads, document verification, cultural news management, and online cultural information services. System evaluation was conducted using Black Box Testing and User Acceptance Testing (UAT). The results of Black Box Testing indicated that all system functions operated according to the specified functional requirements. Furthermore, the UAT results involving 20 respondents achieved a total score of 654 out of a maximum score of 700, resulting in a user acceptance rate of 93.4% and an average score of 4.67 out of 5, categorized as Very Good. These findings demonstrate that the system is capable of supporting cultural documentation and legal document management in a more structured, accessible, and digitally archived manner. The contribution of this study lies in providing an integrated digital platform that combines cultural documentation and legal document management to support the sustainable preservation of Reyog Ponorogo cultural heritage.